Scanning electron microscopy study of surface morphology of Ni3Pb2S2 thin films - Ho, Soon Min (Asian Publication Corporation, 2015)
Ni3Pb2S2 thin films have been prepared using a simple and economical chemical bath deposition method. These films were produced from aqueous solutions in the presence of complexing agent. The morphologies of Ni3Pb2S2 films were characterized using scanning electron microscopy. Scanning electron microscopy micrographs revealed that there are many various morphologies were obtained on the films deposited under various deposition conditions such as pH, deposition time and bath temperature.